The Responsibilities of the Board of Directors in Limited Liability Companies: A Comparative Analysis of the Business Judgment Rule in the United States, the Netherlands, and Indonesia - Sinaga, Viator Harlen; Lumbuun, T. Gayus; Latief, Abdul; Budiman, Anwar (Justice Voice, 2024)
Civil liability of directors involves managing and representing limited liability companies under the doctrine of the business judgment rule, which originated in the United States within the common law system and is examined in civil cases. In contrast, Indonesia, following the civil law system, holds directors of State-Owned Enterprises (SOEs) accountable for company mismanagement that leads to state losses, typically addressed in criminal cases, such as corruption. However, this responsibility is also linked to the business judgment rule. Directors make business decisions aligned with the company’s goals and objectives (intra vires), but such decisions can also result in breaches of fiduciary duties, leading to company losses. The business judgment rule, as practiced in the United States, is reflected in Law No. 40/2007 and influenced by the Dutch Civil Code. Directors’ actions that result in losses are generally not subject to liability, as long as these actions are executed in accordance with their fiduciary duties and the principles of the business judgment rule.